PEMANFAATAN MEDIA LEMBAR KERJA SISWA (LKS) UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI KELAS X SMK PESANTREN SABILIL MUTTAQIEN (PSM) RANDUBLATUNG KABUPATEN BLORA - Eko Nur Syafi'i, Muhammad (Jurnal Studi Islam dan Sosial, 2020)
Result of study is one of the benchmarks that can be used to determine the level of success of learning process. The student’s results of study, especially accounting education as the subject have not been optimized. The result of studying accounting education can be improved by applying some ways. One of them is that by utilizing the Student Worksheet Media as the media. The problems in holding this kind of research are (a) can the utilizing of Student Worksheet Media improve the result of studying accounting education of the tenth grade students in SMK PSM Randublatung?, and (b) how big the improvements of the result of studying Accounting Education of the tenth grade student in SMK PSM Randublatung by utilizing the Student Worksheet Media? This research is a kind of experimental research. The objects of this research are the tenth grade students of SMK PSM Randublatung taking accounting expertise as their program. The class X Accounting 3 is the experimental class and the class X Accounting 4 is the control class. The methods of collecting the data are test and observation. The data analyses are descriptive analysis, the test of normality, the test of hypothesis, and the test of improvement of the result of study. Based on the result of data analyses, the average mark of the students who utilize the Student Worksheet Media has significant improvement. Based on statistics, the Independent Sample of T-Test table shows that there is difference between the results of the study of students who utilize the Student Worksheet Media with the result of study of students who utilize only note book. The conclusion of this kind of research is that the learning process which utilizes the Student Worksheet Media can improve the result of study especially in accounting education. The suggestions that can be given are (a) teacher should utilize Student Worksheet Media as the media in order to improve the result of study especially in Accounting Education. (b) teachers should be able to improve their own materials of education related to the media of studying accounting education.